Transmission of mitochondrial DNA disorders: possibilities for the elimination of mutated mitochondria - Fulka, Josef; Fulka, Helena; John, Justin C St (Cloning and stem cells, 2007)
The recent article by D.T. Brown et al. (2006) discusses the transmission of mitochondrial DNA disorders. In the second part, the authors describe certain techniques that can be potentially used to eliminate the transmission of mutated mtDNA from mother to offspring. It is our opinion that this brief account needs broader explanation. Moreover, some approaches mentioned are not always correctly interpreted.
Keywords: Genetic Diseases, Inborn; mitochondriální nemoci; genetická terapie; mitochondriální DNA; DNA, Mitochondrial; Mutation; mutace; lidé; Mitochondrial Diseases; Humans; Genetic Therapy; genetické nemoci vrozené